Fabrication of Micro Structured Dental Implant Abutments for Optimized Soft Tissue Integration - Doll P. W.; Semperowitsch C.; Häfner M.; Ahrens R.; Spindler B.; Guber A. E. (Current Directions in Biomedical Engineering, 2018)
Within this work we demonstrate a UV-Lithography based method for the fabrication of microgrooves on titanium surfaces. The microgroove period, depth and profile form are easily controllable by process parameters. By controlled under-etching of a lithographically structured photo resist, different profile forms from nearly rectangular, over curvy/spiked to sinus-shaped forms with different amplitudes and sizes can be realized. The resulting microgrooves can be directly used as implant or implant abutment surfaces to enhance soft tissue integration or to create molds for cell/substrate interaction studies. Due to the lithographic process the whole method is highly controllable and reproducible.